Mont Ida, Anderson County - Weers, Clarissa (Kansas State University, The Chapman Center for Rural Studies, 2016)
This study illustrates the instant town of Mont Ida, Washington Township, in Anderson County and its establishment of the Missouri Pacific railroad, peaceful people, and local support that thrived until the decline of trains and neighboring competition. Maps, archived photos and new photos are featured to demonstrate the persistence of the small agricultural community.
Clarissa Weers, “Mont Ida, Anderson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/176.
Keywords: Anderson County; Mont Ida; Oneida; Washington Township; Missouri Pacific Railroad; Westphalia